Principal Leadership in Developing Administrative Staff Competence: A Case Study of the Center of Excellence Vocational School - Victorizal Victorizal; Manap Somantri; Syafryadin Syafryadin; Azizatul Khairi (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
This study aims to analyze the leadership of school principals in developing the competencies of school administrative staff at SMK Negeri 1 Bengkulu Selatan as a Center of Excellence Vocational School. The research uses a qualitative approach with a case study design involving six participants, consisting of one principal, one school administrative staff head, and four school administrative staff. Data were collected through in-depth interviews, observations during four weeks of school hours, and documentation studies, then analyzed through data reduction, data presentation, and conclusion drawing. The results of the study show that leadership is manifested through vision development, routine supervision and evaluation every semester, implementation of needs-based education and training, provision of feedback, resource development, strengthening of cooperation, and development of a school culture based on 6S values. school administrative staff competencies have met the standards of Permendiknas Number 24 of 2008, but there is a gap in ICT competencies, where out of 25 school administrative staff, only 15 are proficient in using computer applications, so 40% still need strengthening. Limited BOSP budgets are also a factor hindering professional development.